Treatment rationale and design of the SPIRAL study: A phase II trial of osimertinib in elderly epidermal growth factor receptor T790M-positive nonsmall-cell lung cancer patients who progressed during prior EGFR-TKI treatment - Uchino, Junji; Nakao, Akira; Tamiya, Nobuyo; Kaneko, Yoshiko; Yamada, Tadaaki; Yoshimura, Kenichi; Fujita, Masaki; Takayama, Koichi (Medicine (Baltimore), 2018)
Advances in epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) treatment led to research on the mechanism of the resistance have revealed that an occurrence of T790M gene mutation generated in exon 20 of the EGFR gene is associated with approximately 50% to 60% of observed resistance. Osimertinib, a 3rd-generation EGFR-TKI, has been shown to be effective against both EGFR tyrosine kinase inhibitor-sensitizing and T790M resistance mutations. In this study, we prospectively investigate the efficacy and safety of osimertinib in elderly patients aged ≥75 years, with ineffective prior EGFR-TKI treatment or with recurrence of EGFR-TKI mutation-positive or T790M mutation-positive nonsmall-cell lung cancer. In total, 35 subjects of both sexes aged ≥75 years with T790M mutation will be included. Participants with pulmonary disorders such as idiopathic pulmonary fibrosis, interstitial pneumonia, pneumoconiosis, active radiation pneumonitis, drug-induced pneumonia, and symptomatic brain metastasis will be excluded. Eligible patients will be administrated osimertinib (80 mg/d) until disease progression. The primary outcome is antitumor effect (objective response rate). The secondary outcomes are progression-free survival, overall survival, disease control rate, and safety. The protocol was approved by the institutional review boards of Kyoto Prefectural University of Medicine and all the participating hospitals. Written informed consent was obtained from all patients before registration, in accordance with the Declaration of Helsinki. Results of the study will be disseminated via publications in peer-reviewed journals. Trial registration number = UMIN000022553.